Market miracles: Resilience of Karachi stock exchange index against terrorism in Pakistan - Mosab I. Tabash; Umaid A. Sheikh; Muzaffar Asad (Cogent Economics & Finance, 2020)
Terrorism plays a pivotal role in influencing the stock indexes of many countries. This research article claims to be first in accessing the asymmetrical effect of multiple categories of terroristic activities on stock indexes in the presence of macroeconomic volatility. This research utilized a Non-linear autoregressive distributive lag model (NARDL) to find out the asymmetrical relationship between terroristic disruptions and stock indexes. Data on terroristic attacks have been incorporated from 2002 to 2015, and more than 4600 observations taken into account. Positive shocks to attacks on mosques, killed in mosque attacks, killed in drone attacks, and army personal fatalities are negatively affecting the stock prices in the short run. Results indicated that such disruption causes a temporary negative effect on stock indexes only in the short run but in the long-run stock exchange remains resilient against such disruptions.
Keywords: 330; NARDL and BDS test of non-linearity; stock exchange resilience; terrorism and macroeconomic volatility; terrorism and stock indexes; terrorism in Pakistan and stock market performance